Tourists or Pilgrims: Classification of the Visitors at the Baptism Site of Jesus Christ in Jordan - Al Zoubi, Mohammad Ibrahim; Ibrahim, Yahaya (International Review of Management and Marketing, 2020)
The purpose of the present study about the baptism site of Jesus Christ together with the holy site portrayal, diverse aspects of the visits to the Baptism Site such as statistics, demographic features of the visitors, their motivations and practices, In addition, classifying the visitors on the site, accordingly, the research aimed to depict the reasons and motivations driving the visits to the baptism site, and examining the potential outcomes of the classification of the visitors at the holy site. 200 surveys have been handed out among Jordanians Christians visitors of which 120 were completed and valid. Accordingly, visitors have been classified into five groups of Religious journeys (pilgrims), Cultural-Pilgrimage tourists, Historical-Pilgrimage tourists, Secular tourists, and Educational tourism. Keywords: Jordan, Religious tourism, the baptism, Religious pilgrimage. JEL Classifications: Z32, Z31, Z39, Z12, N35 DOI: https://doi.org/10.32479/irmm.8893